Hi there! Thank you for the opportunity to help you with your question!

-2b - 2(b+2) = -8 - (3b+8)

We start on the left hand side, distributing the "-2" term into the parenthesis, and on the right hand side, distributing the negative into the parenthesis:

-2b -2b -4 = -8 - 3b - 8

Now, we collect the like terms (terms involving b on the left hand side, and -8-8 is -16 on the right hand side)

-4b -4 = -3b -16

Now we add 4b to both sides:

-4 = b - 16

Finally, we add 16 to both sides:

12 = b

Please let me know if you need any clarification. Always glad to help!